Application of Data Mining Technology in Enterprise Digital Human Resource Management. (22nd June 2022) - Zhou, Da
Abstract : The purpose of this paper is to explore the practical application of big data comprehensive mining and analysis technology in the overall human resource management work of the entire enterprise under the gradual increase in the amount of enterprise data, so as to effectively improve the overall core strategic competitiveness of the entire enterprise and improve the overall human resource management level of the entire enterprise. This article adopts the risk management theory of quantifying the characteristics of business management data, analyzes various management models in modern human resource information system management, and analyzes the entire process of modern enterprise daily operation and various types of human resource system risk management and business data. Combined with quantitative management theory, it introduces the basic concepts of business data feature mining system theory and its most common six data analysis and calculation methods. The module design examples are organically combined, and the traditional data mining analysis theory and its application are extended to the enterprise human resource project management information system. Finally, the experimental results show that the use of big data mining and analysis technology can solve the problems of human resource quality management in small- and medium-sized enterprises. The independent quantitative data mining analysis model has achieved 25% improvement in the application effect of the analysis of the types of human resources in management enterprises, the prevention of internal talent loss in management enterprises, and the performance evaluation management system of enterprises.